A8.04 The histone methyltransferase dot1l is essential for growth and homeostasis of the articular cartilage. (24th February 2016) - Monteagudo, S; Cornelis, F; Storms, L; Lories, RJ
Abstract : Background and objectives: DOT1L is the only known H3K79 histone methyltransferase. Genome-wide association and functional studies identified the DOT1L gene to be associated with cartilage thickness and hip osteoarthritis (OA) and showed an interaction of DOT1L with canonical Wnt signalling. Variations in the DOT1L gene are also associated with human height. These findings and our earlier in vitro insights prompted us to investigate the impact of DOT1L loss of function in vivo . Methods: We generated a conditional cartilage-specific knockout (KO) model of DOT1L by crossing Dot1l fl/fl mice with Col 2 -Cre +/- mice. The deletion of exon2 in the Dot1l gene in cartilage was confirmed by PCR. We performed skeletal staining to identify skeletal abnormalities and growth defects, and histology of the growth plate. To study if the absence of DOT1L activity causes the development of early OA, we injected the chemical DOT1L inhibitor EPZ-5676 intra-articularly in the right knee of 8-week-old wild-type C57Bl/6 mice. Severity of disease was determined by histological scores on sections throughout the knee. Both cartilage damage and synovial hyperplasia were assessed based on OARSI guidelines. Based in our in vitro observations, we analysed the effect of DOT1L loss of function on specific Wnt target genes in either DOT1L cartilage-specific KO mice or in mice injected with EPZ-5676, by immunohistochemistry. Results: A growth defect resulting in short stature became quickly apparent and resulted in mortality from the age of 4-weeks onwards in Dot1l cartilage-specific KO mice. These DOT1L deficient mice exhibited changes in the growth plates with a reduced and disorganised proliferative and pre-hypertrophic zone. In mice injected with EPZ-5676, histology severity scores were significantly increased over time compared to control treatment groups. We confirmed the regulatory role of DOT1L on canonical Wnt signalling in cartilage, since the absence of DOT1L activity in either cartilage specific KO mice or mice injected with DOT1L inhibitor resulted in increased protein levels of specific Wnt target genes. Conclusions: Our findings support an essential role for DOT1L in growth and cartilage homeostasis as a key regulator of canonical WNT signalling in the joint.